Discovering Affecting Factors on Oral Communication of EFL Learners - Farhan, Muhammad; Dahnilsyah, Dahnilsyah; Novitri, Novitri (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Speaking is a crucial communicative competence in English as a Foreign Language (EFL) context. This study aims to investigate internal and external factors influencing students’ daily use of oral English in the English Study Program at Universitas Riau. This study employed an explanatory sequential mixed-method design. Quantitative data were collected via a validated 30-item questionnaire administered to 75 sophomore students, followed by Focus Group Discussions (FGDs) to explore qualitative insights. Data were analyzed using SPSS (descriptive statistics) and thematic analysis. The findings revealed that internal factors, such as anxiety, self-efficacy, motivation, vocabulary, pronunciation, fluency, accuracy, and grammar, continue to shape students’ spoken English practices. Psychological barriers such as fear of judgment and low confidence were present but not dominant. Linguistic barriers, especially limited vocabulary and pronunciation issues, emerged as more prominent. Externally, limited practice opportunities, passive classroom interaction, and curriculum-practice misalignment reduced students’ exposure to real-life spoken English. The integration of findings suggests that while psychological and cultural resistance to speaking English is relatively low, linguistic and environmental challenges remain significant. The lack of supportive speaking environments and communicative pedagogies hampers students’ ability to apply English meaningfully outside the classroom. At last, addressing the underuse of oral English among EFL learners requires targeted pedagogical interventions and curriculum reforms that embed practical oral activities and foster positive peer-speaking culture.